The Role of Community Engagement of Bina Anggita in Increasing Social Environment Awareness - Arga Aulia Rahman; Nunik Hariyanti (Jogjakarta Communication Conference (JCC), 2024)
Humans interact by communicating with each other, or by giving signs that normal humans can understand. However, this is not the case for some people who have special needs. For people who have special needs, carrying out the process of interacting and communicating with individuals and groups is certainly not easy. Children with autism also experience difficulties interacting and communicating with other people. Autistic children show behavioral problems such as self-harm, aggression and tantrums (fussiness). The focus of SLB Bina Anggita is to have a role in providing information to the public about the personalities of autistic children and how to deal with autistic children who have tantrums. The lack of information in some communities regarding autistic children makes it difficult for some communities to overcome problematic behavior in autistic children. This is where the important role of SLB Bina Anggita is played. This research uses a qualitative descriptive method with interview, observation and documentation data collection techniques. The research results show that SLB Bina Anggita has a main role as a contact person for the community, as for information from SLB Bina Anggita. The form of interpersonal communication for autistic children is divided into two, namely nonverbal communication and verbal communication. In verbal communication, autistic children tend to use sign language such as hand movements and foot movements. When interacting at school, autistic children will listen to directions from the teacher to be able to interact, but if autistic children do not focus on the directions given, it will be difficult for the teacher and the surrounding environment to invite the child to interact. During the interaction, it was found that several autistic children still used tools to communicate..